(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the role of the mahalla institute in improving the socio-spiritual environment, forming civil society, and ensuring social stability in New Uzbekistan. The mahalla has been operating as an important educational, spiritual, and social institution in the life of society, based on historical and national values. In particular, within the framework of the reforms being implemented by the President of the Republic of Uzbekistan, Sh.M. Mirziyoyev, the legal status of the mahalla is being strengthened and its powers are being expanded. The article highlights practical measures to stabilize the socio-spiritual environment in mahallas, prevent crime and family breakups, support women, and improve youth education using the example of the Andijan region. The issues of transforming the mahalla institute into a truly civil society institution are also scientifically and theoretically substantiated. Keywords: neighborhood, civil society, socio-spiritual environment, self-government bodies, reforms, women, youth education, social stability